Microwave N2-Ar plasmas applied for N-graphene post synthesis. (17th August 2018) - Bundaleska, N; Bundaleski, N; Dias, A; Dias, F M; Abrashev, M; Filipič, G; Cvelbar, U; Rakočević, Z; Kissovski, Zh; Henriques, J; Tatarova, E
Abstract: High level of nitrogen doping (∼25%) of free-standing graphene sheets was achieved using the remote region of a Ar-N2 microwave plasmas. The relation between the percentage of nitrogen in the plasma and the characteristics of the treated samples has been investigated. Structural changes, being mainly created at the surface of graphene, increase significantly with the percentage of nitrogen in the gas mixture. For a mixture containing 5% of N2 about 2.7 at. % of nitrogen was incorporated in the form of imide group and graphitic bonds (70%), and as N bound to sp3 carbon (30%). Increasing the nitrogen amount to 40% results in the production of samples with up to 25% of incorporated nitrogen. Formation of new types of carbon-nitride structures has also been observed. Detailed x-ray Photoelectron Spectroscopy and Transmission Electron Microscopy analysis support the hypothesis that a structure similar to β -C3 N4 has been synthesized.